Haldane Unrevealed - Schneiderman, David (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2012)
When historians proffer historical truths they “must not merely tell truths,” they must “demonstrate their truthfulness as well,” observes Hackett Fisher. As against this standard, Frederick Vaughan's intellectual biography of Richard Burdon Haldane does not fare so well. Vaughan argues that Viscount Haldane’s jurisprudential tilt, which favoured the provinces in Canadian federalism cases before the Judicial Committee of the Privy Council, was rooted in Haldane’s philosophizing about Hegel. He does so, however, without much reference to the political and legal currents within which Haldane thought, wrote, and thrived. More remarkably, Vaughan does not derive from his reading of Haldane and Hegel any clear preference for the local over the national. We are left to look elsewhere for an explanation for Haldane’s favouring of the provincial side in division-of-powers cases. Vaughan additionally speculates about why Haldane’s predecessor Lord Watson took a similar judicial path, yet offers only tired and unconvincing rationales. Vaughan, lastly, rips Haldane out of historical context for the purpose of condemning contemporary Supreme Court of Canada decision making under the Charter. Under the guise of purposive interpretation, Vaughan claims that the justices are guilty of constitutionalizing a “historical relativism” that Vaughan wrongly alleges Hegel to have propounded. While passing judgment on the book’s merits, the purpose of this review essay is to evaluate the book by situating it in the historiographic record, a record that Vaughan ignores at his peril.